THE INFLUENCE OF SERVICE QUALITY DIMENSIONS TOWARD STUDENTS’ SATISFACTION AT INTERNATIONAL UNDERGRADUATE PROGRAM, UNIVERSITY OF BRAWIJAYA MALANG - Maknun, Mutiara (Jurnal Ilmiah Mahasiswa FEB, 2016)
The purpose of this research is to analyze the influence of service quality dimensions in International Undergraduate Program, Faculty of Economics and Business, University of Brawijaya, Malang. Specifically, the research used SERVQUAL model (Tangible, Empathy, Reliability, Responsiveness, and Assurance) as a tool to measure quality service and multiple linear regression analysis as a method to find relationship between independent and dependent variables. A total of 133 students from three different departments (Accounting, Management and Economics Development) in International Undergraduate Program are used as population and samples in this research.The research type in this study is using quantitative approach with emphasizing hypotheses in explanatory research.The data collection method are gathered by distributing questionnaires through probability sampling. This study uses F test and t testto test the hypotheses in the research. The results found that among five independent variables; Tangible and Empathy have a significant influence to students’ overall satisfaction, whlist  Reliability, Responsiveness, and Assurance do not significantly affect on students’ overall satisfaction.Keywords:Service Quality Dimension, student satisfaction, higher education institution, tangibility, empathy, responsiveness, reliability, assurance.